GEOCHEMISTRY OF LATE MESOZOIC-CENOZOIC BASALTS IN YITONG-DATUN AREA, JILIN PROVINCE AND ITS IMPLICATION - Zhang H.H.; Xu Y.G.; Ma J.L.; Ge W.C. (My University, 2006)
Yitong-Dataun region where, volcanic activity persisted for over 80Ma, provides important on the evolution of deep lithosphere beneath this part of Northeast China. From late Cretaceous (92.5Ma) Datum basalt in Changchun to tertiary (31Ma, 9 ~ 15Ma) basalts in basalts in Yitong-Shulan graben, alkaline contents and Dy/Yb ratios increase with temporal decrease, and the final melting depths of basalts, estimated according to the mantle dynamic melting model,increase from about 50km to 110km. Based on the lithospheric lid effect, the thickness of the lithosphere beneath Yitong-Datun is inferred to have increased since the late Cretaceous. The Yitong Tertiary alkali basalts show a homogeneous composition with trace element spidergram, Nb/U ratio, low (87Sr/86Sr)i and positive ε Nd (t) similar to oceanic island basalts (OIB). All these indicate that Tertiary basalts were derived from an asthenospheric source. In contrast, the Datun tholeiitic basalts have relatively higher Ni, Cr, Sc, Ba/Th, Rb/Nb, Ba/Nb, (87/86Sr)i and lower (143Nd/144Nd), compared to Tertiary alkali basalts. This difference is attributed to the reaction between asthenospheric melts and old enriched-lithospheric mantle. The geochemical characteristics of the Yitong-Datun basalts highlight the different roles of the lithosphere in intraplate magmatism. For the Tertiary basalts, the lithosphere acted as a mechanical barrier to upwelling mantle, but has not been involved materially in the magma generation. For the late Cretaceous basalts, the lithosphere played both indirect and direct roles in magmatic genesis.
Keywords: GEOCHEMISTRY; JILIN; LITHOSPHERIC EVOLUTION; MANTLE DYNAMIC MELTING MODEL; MELT-LITHOSPHERE INTERACTION; MELTING DEPTH; YITONG-DATUN; Мезозой::Меловая; Mesozoic::Cretaceous